Ambient and laboratory observations of organic ammonium salts in PM1. (5th June 2017) - Schlag, P.; Rubach, F.; Mentel, T. F.; Reimer, D.; Canonaco, F.; Henzing, J. S.; Moerman, M.; Otjes, R.; Prévôt, A. S. H.; Rohrer, F.; Rosati, B.; Tillmann, R.; et al.
Abstract : Ambient measurements of PM1 aerosol chemical composition at Cabauw, the Netherlands, implicate higher ammonium concentrations than explained by the formation of inorganic ammonium salts. This additional particulate ammonium is called excess ammonium ( e NH4 ). Height profiles over the Cabauw Experimental Site for Atmospheric Research (CESAR) tower, of combined ground based and airborne aerosol mass spectrometric (AMS) measurements on a Zeppelin airship show higher concentrations of e NH4 at higher altitudes compared to the ground. Through flights across the Netherlands, the Zeppelin based measurements furthermore substantiate e NH4 as a regional phenomenon in the planetary boundary layer. The excess ammonium correlates with mass spectral signatures of (di-)carboxylic acids, making a heterogeneous acid–base reaction the likely process of NH3 uptake. We show that this excess ammonium was neutralized by the organic fraction forming particulate organic ammonium salts. We discuss the significance of such organic ammonium salts for atmospheric aerosols and suggest that NH3 emission control will have benefits for particulate matter control beyond the reduction of inorganic ammonium salts.